IMPLEMENTASI LAYANAN FISIOTERAPI OLAHRAGA PADA KEJUARAAN BULUTANGKIS UNTUK MENDUKUNG PENCEGAHAN DAN PENANGANAN CEDERA ATLET DI KOTA BANJARMASIN - Akhmad Ridhani; Rizky Ridhayanti; Utomo Wicaksono; Dadan Prayogo (Jurnal Pengabdian Masyarakat Berkelanjutan, 2026)
Sports injuries are one of the problems that often occur in badminton athletes due to the high demands of physical activity during matches. The existence of sports physiotherapy services is needed to support efforts to prevent and handle injuries quickly and appropriately. This community service activity aims to implement sports physiotherapy services at the Inter-Catholic Church Badminton Championship throughout South Kalimantan. The method used is in the form of sports physiotherapy coverage through injury prevention education, sports physiotherapy consultations, installation of preventive taping, musculoskeletal assessments, and handling of acute injuries during matches. The activity was carried out by lecturers and students of the IKES Artificial Asylum Physiotherapy Undergraduate Study Program. A total of 25 athletes took advantage of the physiotherapy services provided. The most common types of services provided are sports physiotherapy consultations, preventive taping, muscle cramp management, ankle sprains, and muscle strains. This activity shows that sports physiotherapy services play a role in supporting athlete safety, increasing injury prevention efforts, and helping to handle injuries quickly during the match.